Brain Abscess in Young Adult with Double Outlet Right Ventricle (DORV): A Case Report - Hendry Purnasidha Bagaswoto; Rendi Asmara; Hasanah Mumpuni (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2016)
Intracranial lesions frequently occur in association with congenital malformation of the heart. Intracranial abscess and cerebral thrombosisare the two most serious complications of the brain due to congenital cyanotic heart disease. We reported a case of brain abscess occurring in patients with double outlet right ventricle (DORV). The identification of focal infection and appropriate treatment with parenteral antibiotics,steroid, antiplatelet and anticonvulsant improved patients clinically.Keywords: brain abscess; congenital; double outlet right ventricle